Viscosity and Structural Relaxation of Silver-doped (GeS2)50(Sb2S3)50 - Včeláková, Michaela; Košťál, Petr; Honcová, Pavla (Elsevier Science BV, 2022)
The viscosities of Agx[(GeS2)50(Sb2S3)50]100-x glasses and undercooled melts for x = 5, 7.5, and 15 are studied in the range of 10E6–10E13 Pa·s. The measurements are recorded using a thermomechanical analyzer and two experimental setups, the parallel-plate and penetration methods. The structural relaxation of the composition Ag10[(GeS2)50(Sb2S3)50]90 is studied using differential scanning calorimetry and thermomechanical analysis. The enthalpy and volume relaxation are characterized and described using the Tool-Narayanaswamy-Moynihan (TNM) model. It is verified that both the enthalpy and volume relaxation can be described using similar values of the TNM model parameters. The parameters characterizing the viscous flow and structural relaxation, and their relationship, are discussed.
Viskozita a strukturní relaxace stříbrem dotovaného (GeS2)50(Sb2S3)50
Keywords: chalcogenides; glass; structural relaxation; TNM model; viscosity; chalkogenidy; sklo; strukturní relaxace; TNM model; viskozita